Workbook 1 Smart Choice With Self-study listening /Ken Wilson - Wilson Ken (New York :OXFORD, 2014)
The Smart Choice Workbook is the perfect self-study companion to the Smart Choice Student Book, providing additional practice for all course vocabulary and grammar as well as extra reading, listening, and pronunciation practice.
1.How was your vacation 2.I thing is is exciting 3.Do it Before you are 30
incluye índice
Col. Educ
Keywords: 1.WHERE IS THE PARTY 2.YOU SHOULD TRY IT 3. I USED TO SING